Ammonia Scavenging Prevents Progression of Fibrosis in Experimental Nonalcoholic Fatty Liver Disease. Issue 3 (15th October 2019) - De Chiara, Francesco; Thomsen, Karen Louise; Habtesion, Abeba; Jones, Helen; Davies, Nathan; Gracia‐Sancho, Jordi; Manicardi, Nicolò; Hall, Andrew; Andreola, Fausto; Paish, Hannah L.; Reed, Lee H.; Watson, Abigail A.; et al.
Abstract : Background and Aims: In nonalcoholic fatty liver disease (NAFLD), fibrosis is the most important factor contributing to NAFLD‐associated morbidity and mortality. Prevention of progression and reduction in fibrosis are the main aims of treatment. Even in early stages of NAFLD, hepatic and systemic hyperammonemia is evident. This is due to reduced urea synthesis; and as ammonia is known to activate hepatic stellate cells, we hypothesized that ammonia may be involved in the progression of fibrosis in NAFLD. Approach and Results: In a high‐fat, high‐cholesterol diet–induced rodent model of NAFLD, we observed a progressive stepwise reduction in the expression and activity of urea cycle enzymes resulting in hyperammonemia, evidence of hepatic stellate cell activation, and progressive fibrosis. In primary, cultured hepatocytes and precision‐cut liver slices we demonstrated increased gene expression of profibrogenic markers after lipid and/or ammonia exposure. Lowering of ammonia with the ammonia scavenger ornithine phenylacetate prevented hepatocyte cell death and significantly reduced the development of fibrosis both in vitro in the liver slices and in vivo in a rodent model. The prevention of fibrosis in the rodent model was associated with restoration of urea cycle enzyme activity and function, reduced hepatic ammonia, and markers of inflammation. Conclusions: The results of this study suggest that hepatic steatosis results in hyperammonemia, which is associated with progression of hepatic fibrosis. Reduction of ammonia levels prevented progression of fibrosis, providing a potential treatment for NAFLD.